Administrative Management and Quality of Service of the Administrative Area of the District Municipality of Samán, Puno - Peru - Ticona-Carrizales, Lucio; Rodríguez-Limachi, Omar Moisés; Rodríguez-Chokewanca, Ingrid Rossana; Segales, Betty Campos; Arpasi-Lima, Wilson Smith; Yapuchura-Saico , Cristóbal Rufino (Journal of Ecohumanism, 2024)
In the Samán District Municipality, inefficient administrative management was identified, as evidenced by user complaints about poor service. The objective was to analyze the relationship between administrative management and service quality in 2022. A quantitative methodology and a non-experimental-transversal design were used to observe the phenomena at a specific time. The total population consisted of 9642 inhabitants of the Samán district and stratified probability sampling was used, resulting in a sample of 189 inhabitants of the Samán district. Of this sample, surveys were conducted in six population centers, including Muni Grande (15 users), Jasana Grande (23), Chucaripo (58), Quejón Mocco (37), San Juan de Chacamarca (29) and the town of Samán (27). Data were collected through surveys using two structured questionnaires based on a Likert rating scale. Data were collected by means of two structured questionnaires based on a Likert scale. Microsoft Excel and IBM SPSS statistical software were used for data analysis, and Sperman's Rho statistic was used to determine the relationship of the variables. The results indicate a significant mean positive correlation of 0.629 between the study variables. In conclusion, there is a positive relationship of medium magnitude between administrative management efficiency and service quality. The evidence supports the idea that efforts are being made to ensure efficiency and effectiveness in administrative processes to provide quality service.